Main factors affecting the consumer acceptance of argentinean fermented sausages - López, Constanza María (2012)
Microbiological, physicochemical and sensory characteristics of most popular Argentinean fermented sausages were evaluated in order to detect drivers of consumer liking. As a first step, a detailed description of instrumental parameters and consumer liking for fermented sausages was carried out. Furthermore, two multivariate mappings were performed: (1) cluster analysis to identify accepted fermented sausages based on overall acceptance and liking of appearance, aroma, taste and texture and (2) standard discriminant analysis to graphically recognize instrumental parameters that better described acceptance clusters. From these results, three fermented sausages groups with different acceptance patterns were segmented; taste and texture emerged as key sensory parameters and water activity, lightness, total protein, molds and enterococci among the physicochemical and microbiological variables were correlated with consumer liking.